Bushido and the art of living an inquiry into samurai values - Bennett, Alexander (Chiyoda-ku, Tokyo Japan Publishing Industry Foundation for Culture, 2017)
"What is Bushido? What is Budo? How are the culture and traditions of the samurai connected with the modern martial arts? Is the ancient wisdom of Japan's feudal warriors truly relevant in the twenty-first century? If so, how can it be accessed? This book addresses these questions, and is a must read not only for martial artists, but also for those who want to know more about the enigmatic Japanese mind and notions of self-identity"--Back cover.
Zanshin: Lingering mind and the essence of Bushido Koyo-gunkan and the ideal leader Dead ready to live: Hagakure and Budo-shoshinshu Live and let live: the life-giving sword Bushido: the dark and the light.
"Originally published in Japanese under the title Nihonjin no shiranai bushido, by Bungeishunju Ltd. in 2013"--Title page verso.
Incluldes bibliographical references (pages 170-172).
Keywords: Bushido; Samurai -- History